Patients Attitudes' Toward Chairside Medical Screening in a Dental Setting - Nader Navabi; Mahdiyeh Zeynali; Mozhdeh Mansori; Maryam Alsadat Hashemipour; Seyyed Amir Reza Gandjalikhan Nassab (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess patient's attitudes toward chairside medical screening in a dental setting. Material and Methods: In this descriptive-analytic study, subjects referring to the dental school, dental offices, and clinics of Kerman were evaluated. Each subject filled a questionnaire containing demographic data, patient's attitude towards the performance of examination and the medical status of the subjects. The questionnaire consisted of seven main questions and the subjects were asked to rate them from very important (score 5) to not important at all (score 1). Wilcoxon and Mann-Whitney tests and t-test were used. Friedman's nonparametric analysis of variance was used to compare response items within each question. Results: Screening for medical conditions by dentists was important for most of the participants, and it was important for them to be monitored for their medical condition by the dentists. The majority of patients had the will to be screened for each medical condition by the dentists. Male subjects stated skillfulness and professionality (88.4%) as the most important characteristics of the dentist and compassion as the least important one (56.2%). Female subjects stated knowledge of the dentists (96.3%) as the most essential characteristic and compassion as the least important one (85.8%). The will to undertake screening tests was higher in elder subjects. Conclusion: Dental patients have a positive attitude for medical conditions screening. Screening for medical conditions in a dental setting is a new approach, which might be an important contributor to disease control in the general population.